ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SIKAP MAHASISWA KEPERAWATAN SEMESTER V DAN VII TENTANG HUBUNGAN SEKSUAL (INTERCOURSE) PRANIKAH DI PROGRAM STUDI S1 KEPERAWATAN FAKULTAS ILMU KESEHATAN UNIVERSITAS WIRARAJA SUMENEP - Sri Sumarni; Iva Gamar Dian Pratiwi (Wiraraja Medika : Jurnal Kesehatan, 2017)
Teenage association at this time has reached the stage of worrying. All the mass media both electronic and print media by displaying things that could lead to the destruction of morality of the young generation at this time. Teenagers in the past and present are very different and very irrelevant anymore. Data from BKKBN mention that pregnancy rate among adolescent in Indonesia is high enough that 48 out of 1000 adolescents, and 58% teenage girl who get pregnant outside of marriage have desire to have abortion. General Purpose of This Research is To know the factors related to attitude of nursing students of semester V and VII about premarital sexual intercourse at Nursing Study Program Faculty of Health Sciences. This type of research is observational using Cross-Sectional approach. Population taken in this research is nursing student of semester VII at Health Faculty of University of Wiraraja Sumenep counted 128 student. Including male and female students, then simplified back with a slovin formula obtained 100 samples. Using total sampling sampling techniques. Data Analysis Method using Pearson Product Moment correlation test The result of this research is that most of students have medium attitude about 66% toward premarital sexual intercourse, most of students have medium knowledge about 50% about reproduction health, most of students have enough information from mass media as much as 52%. There is a relationship between knowledge with the attitude of students about premarital sexual intercourse (p = 0.012). There is a significant relationship between mass media and student attitude about premarital sexual relationship (p = 0.008)